2008
DOI: 10.3138/cja.27.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Entre les familles et les services formels, le désir des aînés ayant besoin d'aide

Abstract: Sign comprehension is critical for effective driving, responses to warnings, and way-finding. Signs that are poorly comprehended by older people increase accident risk and may compromise independence. This study sought to determine whether iconic sign comprehension suffers in healthy aging and in the presence of cognitive impairment. Additionally, we examined whether the addition of text to iconic signage would increase comprehension in older adults. In Experiment 1, young adults, healthy older adults, and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Both verbal and non-verbal warnings were used, for the following reasons. Older adults have greater difficulty than young adults in understanding messages presented as visual symbols (Scialfa et al, 2008). Like visual symbols, non-verbal auditory warnings are abstract sounds that may not be readily understood.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Both verbal and non-verbal warnings were used, for the following reasons. Older adults have greater difficulty than young adults in understanding messages presented as visual symbols (Scialfa et al, 2008). Like visual symbols, non-verbal auditory warnings are abstract sounds that may not be readily understood.…”
Section: The Current Studymentioning
confidence: 99%
“…Like visual symbols, non-verbal auditory warnings are abstract sounds that may not be readily understood. Without training older adults have greater difficulty comprehending the meaning of product labels and warnings (Hancock et al, 2005), particularly if they are symbolic, complex or involve only symbols or icons without accompanying text (Lesch et al, 2011;Scialfa et al, 2008). In addition, auditory warnings can possibly startle fatigued drivers, leading to a potentially dangerous oversteer reaction (Hancock and Verwey, 1997).…”
Section: The Current Studymentioning
confidence: 99%
“…Symbols alone seem to be less effective. They seem to be better understood when used in combination with text (Gibson et al, 2004;Namazi & Johnson, 1991b;Scialfa et al, 2008). Furthermore, the combination of signposting and ongoing training by staff seems to be effective (Hanley, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted with sign comprehension showed older adults with cognitive impairment had poorer sign comprehension overall and difficulty with wayfinding icons or icons with text (Scialfa et al, 2008). The research was conducted in Canada and aimed to determine whether iconic sign comprehension declines in healthy aging and in the presence of cognitive impairment.…”
Section: Identification Of Bed Spacesmentioning
confidence: 99%
“…Sign comprehension has an impact on effective driving, responses to warnings, and wayfinding which means signs that are poorly comprehended by older people increase accident risk and may compromise their independence. Therefore, the development of comprehensive signs for older adults with a cognitive impairment needs to take into consideration older adults' range of perceptual and cognitive abilities represented in the population (Scialfa et al, 2008).…”
Section: Identification Of Bed Spacesmentioning
confidence: 99%